El "poblamiento español" en la colonización del norte mexicano: la voz de los ingenieros entre la Independencia y la Posrevolución - Gonzalez Milea, Alejandro (2020)
During the Independent era, and to the present day, the colonization in Mexico has received innumerable studies. Nevertheless, the plans and programs evaluation to establish new towns are still depending on static contexts, determined by epoch and territorial frameworks. It is also the case of the criteria that such studies, through decades, use to valorate their effectiveness and pertinence. The true is that, during the transit to the nacional states era, the Spanish Monarchy jurisdictions -as the Provincias Internas- received a lot of proposals, sometimes using old schemes and other times exploring new formulas. Perhaps the settling process condition of that margins permits to explain why the technicians tended to look at old certainties instead of searching for new reasons; in any case, reading from their own texts and drawings the reasonings and choices made, allows us today to understant the cautious and slow transit to another modernity. Thus, since the first years of the independent life until the 1940 decade, it is possible to identify a common layer of projects inspired in the way that Monarchy pushed the borderlands “poblamiento”; it was the same utopia.